Verfahren zum spannungslosen Schalten der Pulswechselrichter-Ausgangsstufe eines indirekten Dreiphasen-AC-AC Matrixkonverters - Schafmeister, Frank; Kolar, Johann

Thermal-electrical modeling and simulation of resonantly operated DC-DC converters based on extended describing function method - Lv, J.; Cao, Z.; Fröhleke, N.; Böcker, Joachim; Yuan, H.; Mi, H. (Proceedings of the 2011 14th European Conference on Power Electronics and Applications)

Control Realization for an Interior Permanent Magnet Synchronous Motor (IPMSM) in Automotive Drive Trains - Peters, W.; Huber, T.; Böcker, Joachim (PCIM 2011, Nürnberg, Deutschland)

Logik und Mathematik in der Philosophie Leonard Nelsons - Peckhaus, Volker (Leonard Nelson – ein früher Denker der Analytischen Philosophie. Ein Symposium zum 80. Todestag des Göttinger Philosophen)

Robert and Hermann Grassmann’s Influence on the History of Formal Logic - Peckhaus, Volker (Hermann Graßmann. From Past to Future: Graßmann’s Work in Context. Graßmann Bicentennial Conference, September 2009)
Rezension: Zbl. Math. 1223.01014 (J. Mackenzie).

Leibniz’ Logik und die sprachliche Erschließung der Welt in der Moderne - Peckhaus, Volker (Departure for Modern Europe. A Handbook of Early Modern Philosophy (1400–1700))

Einleitung: Räume zwischen Materialisierung und Idealisierung - Peckhaus, Volker; Wahrig, Bettina (Berichte zur Wissenschaftsgeschichte)

Frequency / duty cycle current-mode fuzzy control for LCC resonant converter - Hu, M.; Böcker, Joachim; Fröhleke, N. (EPE2011, Birmingham, UK)

Modelling Lexical Alignment in Spontaneous Direction Dialogue Data by Means of a Lexicon Network Model - Mehler, Alexander; Lücking, Andy; Menke, Peter (Proceedings of 12th International Conference on Intelligent Text Processing and Computational Linguistics (CICLing))
We apply a network model of lexical alignment, called Two-Level Time-Aligned Network Series, to natural route direction dialogue data. The model accounts for the structural similarity of interlocutors’ dialogue lexica. As classification criterion the directions are divided into effective and ineffective ones. We found that effective direction dialogues can be separated from ineffective ones with a hit ratio of 96% with regard to the structure of the corresponding dialogue lexica. This value is achieved when taking into account just nouns. This hit ratio decreases slightly as soon as other parts of speech are also considered. Thus, this paper provides a machine learning framework for telling apart effective dialogues from insufficient ones. It also implements first steps in more fine-grained alignment studies: we found a difference in the efficiency contribution between (the interaction of) lemmata of different parts of speech.

Corpus-driven development of a Gesture Typology based on the Bielefeld Speech and Gesture Alignment Corpus - Hahn, Florian; Menke, Peter (Online Proceedings of the Corpus Linguistics 2011 Conference, Birmingham (UK))
We introduce the multimodal Bielefeld Speech and Gesture Alignment (SaGA) corpus, its design, structure, and approaches to a data-driven development and validation of a gesture typology.

The Bielefeld Jigsaw Map Game (JMG) Corpus - Lücking, Andy; Abramov, Olga; Mehler, Alexander; Menke, Peter (Online Proceedings of the Corpus Linguistics 2011 Conference, Birmingham (UK))

From Neural Activation to Symbolic Alignment: A Network-Based Approach to the Formation of Dialogue Lexica - Mehler, Alexander; Lücking, Andy; Menke, Peter (Proceedings of the International Joint Conference on Neural Networks (IJCNN 2011))

From Experiments to Corpora: The Ariadne Corpus Management System - Menke, Peter; Mehler, Alexander (Online Proceedings of the Corpus Linguistics 2011 Conference, Birmingham (UK))

Untersuchung alternativer Erwärmungsverfahren für den Presshärteprozess - Marten, Thorsten; Niewel, J.; Tröster, Thomas (HTM Journal of Heat Treatment and Materials)

Volker Remmert/Ute Schneider, Eine Disziplin und ihre Verleger. Disziplinenkultur und Publikationswesen der Mathematik in Deutschland, 1871–1949. Bielefeld: transcript Verlag 2010 - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)

Mechanical Properties of Fused Deposition Modeling Parts Manufactured with ULTEM*9085 - Bagsik, A.; Schöppner, Volker (ANTEC)
In this work the influence of the orientation and the toolpath generation of manufactured parts based on the mechanical data are analyzed. Tensile Specimen are generated with the given parameters as well as with changing parameters of the native software based upon the CAD data. The parts then are built up with the “Fortus 400mc” from Stratasys. First tensile tests show different strength and strain characteristics that depend on the given structure and as a result of the build direction. The influence of the parameters was analyzed with a statistic test method by using the software Design Expert.

FPGA-Based High Performance AC Drive - Mathapati, S.

A Smelly Body, The Fear of the Unclean Feminine Body: A Cultural Analysis of the Debate on Perversion in Charlotte Roche’s Feuchtgebiete - Lammer, Christina (The Evil Body)

Portfolioarbeit im Fremdsprachenunterricht – Yes, we can! - Ballweg, Sandra; Bräuer, Gerd (Fremdsprache Deutsch 45/2)

Schreibend lehren lernen – unterstützt durch ein digitales Kompetenzportfolio für Lehramtsstudierende (dikopost) - Ballweg, Sandra; Scholz, Nadine; Richter, Kristina; Bruder, Regina (Schreibarrangements in Schule, Studium, Beruf)